Evaluación de la actividad antioxidante y perfil metabolómico en cinco ecotipos de cocona (Solanun sessiliflorum) de la Amazonía peruana 2020 - Merino Zegarra, Claudia (2023)
The fruits of Solanun sessiliflorum "cocona" are consumed as a food and used in traditional medicine, mainly used by the Amazonian population for the elaboration of different food products such as nectars, jams and others. In the present research work, the pulp of five native cocona ecotypes from different geographical locations in the Peruvian Amazon was studied in order to compare the incidence of origin and environment on antioxidant activity and metabolomic profile. The fruits were collected from the IIAP-Huanuco germplasm bank, the pulp of each ecotype was freeze-dried and the extracts were prepared and analysed for antioxidant activity using the DPPH and ABTS free radical scavenging methods, total phenols and total carotenoids, showing higher activity in ecotype CTR (21.92 umol trolox/g), CD1 (25.67 umol trolox/g), CTR (35.79 mg GAE/g) and CD1 (122.65 ug β-carotene/g), respectively. The metabolomic profile was also evaluated and 70 bioactive substances were detected in the different cocona ecotypes, including different phenolic acids, amino acids and flavonoids; of which six were spermidines (peaks 1, 2, 25, 26, 38 and 39), thirteen amino acids (peaks 3, 9, 11-13, 16, 17, 22-24), eighteen flavonoids (peaks 28, 30-32 45, 46, 48-53 56, 57, 61 and 64-66), twelve phenolic acids (peaks 19, 21, 27, 29, 34, 34, 35, 35, 36, 42, 43, 44, 54 and 59), two carotenoids (peaks 62 and 63), eight lipid derivatives (peaks 37, 55, 58, 60 and 67-70), one sugar (peak 47), four terpenes (peaks 33, 40, 41 and 47), two amides (peaks 10 and 18), one aldehyde (peak 15), and three saturated organic acids (peaks 4, 5 and 20).